From cages to cage-free: A qualitative exploration of Chinese egg producers’ views on the opportunities and challenges to adopting cage-free egg production systems in China - Qing Yang; Fritha Langford; Belinda Vigors; Ruqian Zhao; Cathy M Dwyer (Animal Welfare, 2025)
The transition from conventional cage systems to cage-free egg production in China remains limited despite apparently increasing consumer demand for cage-free eggs. This study interviewed 15 large-scale Chinese egg producers using cages and/or cage-free systems (i.e. single-, multi-tier and free-range) to investigate the perceived challenges and opportunities during the transition. The cage farms’ scales range from 110,000 to 30 million, while the cage-free farms keep between 12,000 and 300,000 laying hens. Drawing upon the COM-B model of the Behaviour Change Wheel, this study explored how producers’ Capabilities, Opportunities, and Motivations impact decision-making processes. Key findings reveal that cage and cage-free producers considered consumer demand and profitability as primary drivers for adopting cage-free systems. While free-range producers were more confident in the market, barn system producers faced greater uncertainty due to limited engagement from corporate buyers. Moreover, these cage-free producers believed reliable certification and labelling schemes to be critical for building consumer trust and ensuring the success of cage-free operations. All the participants perceived access to sufficient land and financial resources to be essential for a successful transition. While most studies propose education as a long-term strategy to promote the growth of the cage-free egg sector, our findings are the first to highlight that engaging corporate buyers and establishing trustworthy certification schemes are the most crucial short-term interventions required to drive the development of large-scale cage-free farms and support sustained improvements in animal welfare in China.